The Concept of Children's Education in The Qur'an (Thematic Interpretation Approach) - Ningsih, Titik; Ritonga, Asnil Aidah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the concept of children's education in the Qur'an through the study of thematic interpretation approaches. The terms of children's education discussed are the words tarbiyah and ta'lim. Researchers try to analyze this study with the help of thematic interpretation (maudhu'i) by searching for verses relevant to education. This research is a qualitative type with a library research method. The results of this study indicate that the concept of education for children in terms of tarbiyah and ta'lim is a procedure for developing, maintaining, and fostering children in order to provide scientific readiness and skills for students. This is intended so that the child has a complete and noble personality, and is able to carry out the mandate as a caliph and servant of Allah on earth.